The Effect of Clinical Decision Support System on the Rates of Patients Who Reapply to the Emergency Department with the Same Diagnosis - İlker Köse; Elife Özkan (Genel Tıp Dergisi)
Aim: We aim to decrease readmissions with the same diagnosis within 24 hours in emergency departments when many patients are admitted, such as during a pandemic. Methods: A comparison was made between the quarterly and monthly increases in 2021, 2020, and 2019 during the pandemic period. The root cause analysis determined that non-branch physicians and after-hours visits contributed to the increase in readmissions to the emergency department within 24 hours. A complete digital structure in State Hospital, Hospital Information Management System level 7 has enabled standardized diagnosis by eliminating physician and branch-based differences with the decision support systems established by the Hospital Information System by utilizing digital measures. Cross-sectional and retrospective reapplication rates 2019, 2020, 2021 2nd Period (April, May, June). Quality Standards in Health Emergency Department two data sets were used as The Basic Health Statistics Module data. Result as the 2019, 2020, and 2021 monthly reapplication rates of emergency department 2nd Period (April, May, June) month comparison Application rates 2020-year 2nd Period. Looking at the same months in 2021 and 2020, it is seen that the reapplication rate decreased below 2% within 24 hours. Results: This means that the application rate has returned to pre-pandemic levels. It is aimed at making it easier and more effective to work in situations that lead to collective admissions to emergency hospital services. The same situation has been an example of similar practices within hospital services. Conclusion: The application rate returned to its status outside the pandemic period. Differences in physician-induced approaches to diagnosis and treatment were eliminated, and standardization was achieved.